An Analysis of External Influence Factors of High-emission Passenger Car Consumption in China - LI, GUANLIN (2009)
The market of high-emission passenger car in China was not declined as fast as other countries such as the USA, and there are some external and internal influence factors which caused this phenomenon. This study aims find and define the external influence factors of high-emission passenger car consumption in China, by using of qualitative interview research method. The results show that social, price, brand, culture and reference group and utility influence factors are obviously influence high-emission passenger car consumption behavior in China; social influences have been considered as the most important factors of high-emission passenger car consumption in China, mianzi as an important culture influence factor which has been used to explain most Chinese people’s behaviors and motivations, other regional influences such as fuel price and traffic conditions will have less effect on Chinese consumer’s decision. The results suggest a general understanding of external influence factors and a clear direction which could also can be used by both marketing practitioners and academics.